Ultrasound as a pre-treatment for extraction of bioactive compounds and food safety: A review. (May 2021) - Perera, Conrad O.; Alzahrani, Mona Ahmed J.
Abstract: Application of ultrasound has been considered a "green" technology, because it offers advantages in terms of selectivity, better quality, use of less chemicals, and energy efficiency. Hence, it is well suited for extraction of bioactive compounds from plant and animal materials, which generally require large quantities of organic solvents. In addition to extraction, the inactivation of certain microorganisms, especially the Gram-negative bacteria have been reported in literature. The principle of extraction and inactivation of microorganisms are attributed to the cavitation phenomena. Ultrasound per se is not sufficient to inactivate all microorganisms. Gram-positive organisms are known to have thicker cell walls, and some contain peptidoglycans which are difficult to disrupt. The effects of ultrasound also depend on the type, shape, or diameter of the micro-organisms. Vegetative cells are more susceptible to ultrasound than spore. Enzymes are thought to be inactivated by denaturation of the protein. Many micro-organisms are not inactivated by ultrasound alone but in combination with mild heat or other non-conventional techniques will be highly effective. The combined effects are known to be synergistic rather than additive. Graphical abstract: Image 1 Highlights: US is considered a green technology for extraction of bioactive compounds. Principle of extraction is based on cavitation phenomenon. It is a non-thermal method of destruction of microorganisms. Shows synergy effects in conjunction with mild heat, pressure, and other methods. Offers opportunities to sterilize and make food safe for distribution and consumption.